2013
DOI: 10.2147/tacg.s34116
|View full text |Cite
|
Sign up to set email alerts
|

PALB2 and breast cancer: ready for clinical translation!

Abstract: For almost two decades, breast cancer clinical genetics has operated in an environment where a heritable cause of breast cancer susceptibility is identified in the vast minority of women seeking advice about their personal and/or family history of breast and/or ovarian cancer. A new wave of genetic information is upon us that promises to provide an explanation for the greater proportion of current missing heritability of breast cancer. Whilst researchers refine bioinformatic and analytic methodology necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 68 publications
(99 reference statements)
5
33
0
2
Order By: Relevance
“…7 Additional studies found carriers of truncating mutations with a frequency of ~1−2% in Spanish, Chinese, South African, Russian, German, Italian, AfricanAmerican, Australasian, and Malaysian familial or early-onset breast cancer cases. 10,[20][21][22][23][24] A similar frequency was observed in population-based studies of Australians and mixed-ethnicity breast cancer cases. 20,25,26 A mutation-carrier frequency of 3.4% was reported in familial cases from the United States.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…7 Additional studies found carriers of truncating mutations with a frequency of ~1−2% in Spanish, Chinese, South African, Russian, German, Italian, AfricanAmerican, Australasian, and Malaysian familial or early-onset breast cancer cases. 10,[20][21][22][23][24] A similar frequency was observed in population-based studies of Australians and mixed-ethnicity breast cancer cases. 20,25,26 A mutation-carrier frequency of 3.4% was reported in familial cases from the United States.…”
Section: Introductionsupporting
confidence: 77%
“…10,[20][21][22][23][24] A similar frequency was observed in population-based studies of Australians and mixed-ethnicity breast cancer cases. 20,25,26 A mutation-carrier frequency of 3.4% was reported in familial cases from the United States. This frequency, apparently higher as compared with that reported in other studies, might be due to the examined sample being enriched in a few founder mutations.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations